iCub Whole-Body Control through Force Regulation on Rigid Non-Coplanar Contacts - Nori, Francesco; Traversaro, Silvio; Eljaik, Jorhabib; Romano, Francesco; Del Prete, Andrea; Pucci, Daniele (Frontiers in Robotics and AI, 2015)
This paper details the implementation on the humanoid robot iCub of state-of-the-art algorithms for whole-body control. We regulate the forces between the robot and its surrounding environment to stabilize a desired robot posture. We assume that the forces and torques are exerted on rigid contacts. The validity of this assumption is guaranteed by constraining the contact forces and torques, e.g. the contact forces must belong to the associated friction cones. The implementation of this control strategy requires to estimate the external forces acting on the robot, and the internal joint torques. We then detail algorithms to obtain these estimations when using a robot with an iCub-like sensor set, i.e. distributed six-axis force-torque sensors and whole-body tactile sensors. A general theory for identifying the robot inertial parameters is also presented. From an actuation standpoint, we show how to implement a joint torque control in the case of DC brushless motors. In addition, the coupling mechanism of the iCub torso is investigated. The soundness of the entire control architecture is validated in a real scenario involving the robot iCub balancing and making contacts at both arms.